2007
DOI: 10.1111/j.1479-6988.2007.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing the wandering behaviour of people living in a residential aged care facility

Abstract: Background  Wandering behaviour is frequently seen in older people with cognitive impairment. The prevalence of patients exhibiting wandering behaviour has been estimated to be 11.6% on traditional units and 52.7% on Alzheimer's units. Wandering is one of the core behavioural characteristics that impact on familial carers and is likely to influence the decision to place a family member in an aged care environment. Considering the possible risks associated with wandering behaviour, the successful identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, it is possible that our bespoke assessment of risk of bias for these studies led to conservative conclusions. Indeed, other systematic reviews Hodgkinson et al, 2007;Letts et al, 2007;Padilla et al, 2007) have concluded moderate evidence for the effectiveness of environmental modification strategies on reducing exiting based on several of the same included studies as this review. However, these reviews included the results of other systematic reviews (i.e., each other) as the highest 'levels of evidence', often without methodological appraisal of primary research.…”
Section: Assumptions and Robustness Of Synthesismentioning
confidence: 63%
“…However, it is possible that our bespoke assessment of risk of bias for these studies led to conservative conclusions. Indeed, other systematic reviews Hodgkinson et al, 2007;Letts et al, 2007;Padilla et al, 2007) have concluded moderate evidence for the effectiveness of environmental modification strategies on reducing exiting based on several of the same included studies as this review. However, these reviews included the results of other systematic reviews (i.e., each other) as the highest 'levels of evidence', often without methodological appraisal of primary research.…”
Section: Assumptions and Robustness Of Synthesismentioning
confidence: 63%
“…However, this review concluded that there was insufficient evidence to provide definitive guidelines. Assessment should focus on underlying causes of behaviours and include consideration of the physical, social, psychological and environmental, and the benefits of physical restraint should also outweigh the risks (Hodgkinson, Koch, Nay, & Lewis, 2007). Hantikainen and Kappeli (2000) acknowledged that clinical decision-making was related to the understanding of restraint and the rights and responsibilities of nurses and residents, whereby the decision to use restraint was often unique to a nurse rather than based on policy or evidence.…”
Section: A Restraint-free Environment: Benefits and Barriersmentioning
confidence: 99%